Methane and Nitrous Oxide Productions and Community Structure of Methanogenic Archaea in Paddy Soil of South Sulawesi, Indonesia - OSLAN JUMADI; KAZUYUKI INUBUSHI (Indonesian Society for microbiology, 2012)
The potential of methane and nitrous oxide productions and community structure of methanogenic archaeahas been characterized by incubation studies and PCR-DGGE approaches, respectively. The results showed thataddition of straw into the soil was the most important factor that influenced CH4 production in this incubation 4 experiment, while N2O production was observed higher in soil without straw amendment under saturated 2 condition. Most of the clone sequences revealed from DGGE band was associated with a archaea lineage,Methanocellales ord. nov (Rice Cluster I). Other sequences belong to Methanomicrobiales, Methanosaetalesand Rice Cluster 2 (RC-2). The study also showed that the hydrogenotrophic methanogens were the dominant members in methanogenic archaea community obtained from tropical paddy field soil, while acetoclastic methanogens present in relatively minor quantity in the soil.